Influence of grade heterogeneity and gangue mineralogy on the efficacy of high voltage pulse enabled ore pre-concentration. (1st December 2020) - Huang, Wei; Shi, Fengnian; Antonio, Christian; Runge, Kym
Highlights: Two ore samples were treated by High Voltage Pulse (HVP) and mechanical breakage. Grade heterogeneities were determined to assess ore amenability to pre-concentration. A positive linear correlation between grade heterogeneity and HVP efficacy was observed. Conductive gangue minerals affect the efficacy of HVP enabled pre-concentration. Mechanical breakage presented negligible pre-concentration potential for both ores. Abstract: Variations in the amenability of different ores to high voltage pulse (HVP) enabled pre-concentration has been observed, yet it is unclear which intrinsic properties of the ores caused the variation in HVP efficacy. The objective of this study is to investigate the influence of grade heterogeneity and gangue mineralogy on the efficacy of HVP enabled ore pre-concentration. Two ore samples with different mineralisation were treated with HVP and mechanical impact breakage, respectively. The results showed that Sample A with an intrusive vein-like mineralisation structure exhibited better pre-concentration efficacies for gold and copper after HVP pretreatment compared to Sample B, which had a finely disseminated copper mineralisation structure. Pretreatment by mechanical impact breakage presented negligible metal pre-concentration potential for both ore samples. The Constitution Heterogeneity determined from assaying randomly selected feed particles, showed that Sample A had a significantly greater grade heterogeneity than Sample B. It was found that the gold and copper grade heterogeneities of the two ore samples exhibited a positive linear correlation with the efficacy of HVP enabled pre-concentration. This is a consequence of heterogeneity resulting in distinct populations of mineralised and barren particles, a requirement necessary to achieve selective breakage. It is also proposed that the presence of conductive gangue minerals can play a role on the efficacy of HVP enabled pre-concentration, with the effect being positive or negative depending on whether or not the gangue has an association with the valuable minerals of interest.